Prenatal transportation stress does not impact resting skeletal muscle mitochondrial function or antioxidant activity in Brahman calves - Wesolowski, Lauren T.; Guy, Chloey P.; Long, Charles R.; Randel, Ronald D.; Riley, David G.; Welsh, Thomas H.; White-Springer, Sarah H. (Frontiers in Animal Science, 2023)
In cattle, prenatal transportation stress has been associated with differential methylation of genes related to metabolism but the effects of prenatal transportation stress on skeletal muscle mitochondria and oxidative stress have not been investigated. We tested the hypothesis that prenatally stressed calves would exhibit increased skeletal muscle mitochondrial function resulting in greater oxidative stress than calves from non-stressed dams. Serum and longissimus thoracis muscle samples were collected from yearling Brahman calves whose mothers were stressed by transportation at 5 time points during gestation (PNS; 8 bulls, 6 heifers) and control calves (CON; 4 bulls, 6 heifers). Serum was evaluated for the stress hormone, cortisol, and a marker of muscle perturbation, creatine kinase activity. Muscle samples were analyzed for concentration of a byproduct of lipid peroxidation, malondialdehyde, and activity of the antioxidants, superoxide dismutase and glutathione peroxidase. Additionally, muscle mitochondrial volume density and function were estimated by citrate synthase and cytochrome c oxidase activities, respectively. Data were analyzed using mixed linear models with sex, treatment, and the sex×treatment interaction as fixed effects. No investigated variable differed between CON and PNS calves (P≥0.3). These data suggest that prenatal transportation stress does not impact skeletal muscle mitochondrial metabolism or markers of stress or muscle damage in Brahman yearling calves at rest. However, previously reported negative impacts of prenatal stress on inflammatory responses suggest that PNS calves may be differentially equipped to handle an acute stressor. Future research should investigate the energetic and inflammatory implications of acute stressors in animals subjected to prenatal stress.